Preliminary effects of renal denervation with saline irrigated catheter on cardiac systolic function in patients with heart failure: A Prospective, Randomized, Controlled, Pilot Study. Issue 4 (3rd May 2016) - Chen, Weijie; Ling, Zhiyu; Xu, Yanping; Liu, Zengzhang; Su, Li; Du, Huaan; Xiao, Peilin; Lan, Xianbin; Shan, Qijun; Yin, Yuehui
Abstract : Objective: To assess efficacy and safety of renal denervation (RDN) for heart failure (HF). Background: RDN has been demonstrated to be an effective method in lowing overactive sympathetic nerve. However, it's feasibility and efficacy for HF is unclear. Methods: In this randomized, controlled pilot study, patients with HF were randomly assigned in 1:1 ratio to undergo RDN plus optimal medical therapy (RDN group) or only optimal medical therapy (control group). Before randomization, patients received optimal medical therapy at least half a year. Primary efficacy end point was the change in LVEF over six months; secondary efficacy end points were the change in six‐minute walk distance and SF‐36 Health Survey scores over six months. Results: Up to Apr 2015, sixty symptomatic HF patients were successfully enrolled into study. Thirty patients were randomly assigned to RDN group and 30 patients were randomly assigned to control group. All patients completed six months follow up. During follow up, no severe adverse events were observed. Blood pressure was stable in both groups. Patients in RDN group had shown a significant improvement in LVEF ( P < 0.001), SMWD ( P = 0.043), NYHA class ( P < 0.001), NT‐proBNP ( P < 0.001) and office heart rate ( P = 0.008). Compared with control group, RDN patients were associated with significant improvement in all domains of SF‐36 but bodily pain ( P = 0.74). No significant change in estimate glomerular filtration nor complication of renal artery stenosis were observed. Conclusions: Results imply that RDN could be safely applied to treatment of HF and probably improve cardiac systolic function and patients' quality of life. © 2016 Wiley Periodicals, Inc.